Implementation of the cobas Liat influenza point-of-care test into an emergency department during a high-incidence season: a retrospective evaluation following real-world implementation. Issue 3 (March 2019) - Youngs, J.; Iqbal, Y.; Glass, S.; Riley, P.; Pope, C.; Planche, T.; Carrington, D.
Summary: The cobas Liat influenza A/B and respiratory syncytial virus (RSV) assay (Liat) was used in the adult emergency department of a large London hospital from 21 st January 2018 to 14 th April 2018. Influenza was detected in 308 of 1027 (30%) samples tested; influenza A in 157 (15.3%), influenza B in 149 (14.5%) and RSV in 28 (2.7%). When compared against Fast Track Diagnostics Respiratory Pathogens 21 multiplex polymerase chain reaction and Cepheid Xpert Xpress Flu/RSV assay, Liat performance for the detection of influenza A or B was: sensitivity 85% [95% confidence interval (CI) 76–92)], specificity 98% (95% CI 97–99), negative predictive value 94% (95% CI 92–96) and positive predictive value 95% (95% CI 91–97).